Penguatan Profil Pelajar Pancasila Dalam Implementasi Kurikulum Merdeka Belajar di UPT SPF SD inpres Manggala Kota Makassar - Meliana, Hesti; Amaliyah, Nurhadifah; Supardi, R; Abustang, Perawati Bte (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2024)
Research was carried out to find out how to implement, supporting factors, and inhibiting factors to strengthen the profile of Pancasasila students in implementing the independent curriculum. The type of research used in this research is descriptive qualitative. The research subjects were class IV UPT SPF SD Inpres Manggala. The data collection techniques used are observation, interviews and documentation. The research results obtained in strengthening the Pancasila student profile in implementing the independent curriculum behave in accordance with Pancasila with the existence of several dimensions of the Pancasila student profile and can help students and teachers to produce students who are independent and responsible for their learning processes and outcomes. The supporting factors are the development of character in students, the existence of project-based learning and coaching by teachers and the integration of Pancasila values, and support from parents. Then the inhibiting factors are the lack of understanding of students about how to adapt in learning, limited class time by teachers, teachers' understanding of how to organize learning modules and students' attitudes that lack interest in various subjects so that teachers find it difficult to apply good attitudes and independence to students.